2008
DOI: 10.1029/2008jd010150
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution of the different types of aerosols in the stratosphere: Detection of solid particles and analysis of their spatial variability

Abstract: Stratospheric aerosols play a significant role in stratospheric chemistry. In the past, it was assumed that only liquid droplets are present in the stratosphere. Nevertheless, a few lidar measurements have shown that sudden enhancement of aerosol content in the middle stratosphere could be due to meteoritic debris. Aircraft measurements have shown that solid particles can be found in the lower stratosphere; these particles are mainly soot, but also include some interplanetary material. In order to better docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 70 publications
8
80
0
Order By: Relevance
“…Such dense smoke layers disturb chemical processes, radiative fluxes, and even heterogeneous ice formation in the upper troposphere; this may continue over a period of weeks to several months. The black carbon aerosol partly enriches the natural soot particle reservoir between 20 and 30 km by upward motions (Renard et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such dense smoke layers disturb chemical processes, radiative fluxes, and even heterogeneous ice formation in the upper troposphere; this may continue over a period of weeks to several months. The black carbon aerosol partly enriches the natural soot particle reservoir between 20 and 30 km by upward motions (Renard et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Fromm et al (2000Fromm et al ( , 2003 and Rosenfeld et al (2007) showed that large amounts of fire smoke can be lifted up to the tropopause within a short time period (less than 1 h) and can partly reach the lower stratosphere via the formation of pyrocumulonimbus clouds that are associated with strong updrafts with vertical wind velocities of 10-30 m s −1 (Fromm et al, 2010;Peterson et al, 2017). Self-lifting effects (Boers et al, 2010;Siddaway and Petelina, 2011;de Laat et al, 2012) and gravito-photophoresis forces (Rohatschek, 1996;Pueschel et al, 2000;Cheremisin et al, 2005;Renard et al, 2008) lead to a further ascent of the soot-containing layers.…”
Section: Introductionmentioning
confidence: 99%
“…Aerosol particles counters are often used on the ground; some of them are used in the free atmosphere on-board aircraft or large balloons during dedicated campaigns, for example for the studies of desert dust events or volcanic aerosols (Bukowiecki et al, 2011;Jégou et al, 2013;Ryder et al, 2013) or for stratospheric studies (Rosen, 1964;Ovarlez and Ovarlez, 1995;Deshler et al, 2003;Renard et al, 2008, Renard et al, 2010b. We propose here a new optical particle counter concept called LOAC (Light Optical Aerosol Counter) that is light and compact enough to perform measurements on the ground and under all kinds of balloons in the troposphere and in the stratosphere, including meteorological balloons.…”
Section: Introductionmentioning
confidence: 99%
“…Other minor constituents of stratospheric aerosol include upper tropospheric material such as nitrate, ammonia, organics, minerals and metals (e.g. Talbot et al, 1998;Murphy et al, 1998), or meteoric material (Murphy et al, 2007;Renard et al, 2008), aircraft and rocket exaust (Kjellstrom et al, 1999;Danilin et al, 2001;Jackman et al, 1996). A comprehensive review of the measurements, the importance, and the life cycle of local and global stratospheric aerosol can be found in Deshler (2008).…”
Section: Introductionmentioning
confidence: 99%